Binding of dsRNAs by PNAs containing Q, modified Q and 2-thio Uracil monomers - Lina Nur Lyana Abdul Rahim (2019)
Peptide nucleic acids (PNAs) have been developed as chemical probes and therapeutic ligands in RNA duplex recognition. PNAs bind to ribonucleic acid (RNA) duplexes via complementary Hoogsteen hydrogen bonding to form PNA·RNA2 triplexes. In this study, modifications were made to chemically synthesize the PNA sequences incorporated with Q, modified Q and 2-thio Uracil monomers to target the inverted Watson-Crick C-G base pair present in RNA hairpins. By performing non-denaturing polyacrylamide gel electrophoresis experiment, the specific selectivity and binding interactions between the PNA oligomer and the RNA duplex could be studied. We demonstrated that modified Q monomer displayed a better binding affinity in recognizing C-G base pair than Q monomer due to the replacement of a 5-methyl group in Q with a 5-iodo group in modified Q monomer. In addition, incorporation with 2-thio Uracil brings stabilization to the triplex strands by improving the Hoogsteen hydrogen bonding and stacking interactions. Thus, enhancing the selective interaction with C-G inverted Watson-Crick base pair in RNA duplexes could be done through the combination of modified Q and 2-thio Uracil monomers in PNA sequences.